Responsibility of Land Deed Officials for Issuing Replacement Certificates Due to Loss - Widyasari, Andini; Hafidz, Jawade; Kusriyah, Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
Land title certificates are strong evidence of land ownership, providing legal certainty through the land registration system. In practice, problems often arise in the form of lost land title certificates, including during the processing at the Land Office. This situation causes losses for rights holders and raises legal issues regarding the responsibility of Land Deed Officials (PPAT). This study aims to analyze the procedures for issuing replacement certificates for lost land by the Serang Regency Land Office and the responsibility of PPATs in the event of lost certificates during the land registration process. The research method used was sociological juridical with analytical descriptive specifications. The results showed that the procedure for issuing replacement certificates was implemented in accordance with Government Regulation Number 24 of 1997, while the PPAT's responsibilities were principally administrative and professional as long as there was no element of error or negligence. The research results indicate that the procedure for issuing replacement certificates has been implemented in accordance with statutory provisions, particularly Government Regulation Number 24 of 1997 concerning Land Registration, but administrative obstacles remain. The responsibility of the Land Deed Official (PPAT) is, in principle, administrative and professional as long as there is no element of error or negligence.